A primer on rhythm quantification for fish sounds: a Mediterranean case study. Issue 9 (22nd September 2021) - Burchardt, Lara S.; Picciulin, Marta; Parmentier, Eric; Bolgan, Marta
Abstract : We have used a lately established workflow to quantify rhythms of three fish sound types recorded in different areas of the Mediterranean Sea. So far, the temporal structure of fish sound sequences has only been described qualitatively. Here, we propose a standardized approach to quantify them, opening the path for assessment and comparison of an often underestimated but potentially critical aspect of fish sounds. Our approach is based on the analysis of inter-onset-intervals (IOIs), the intervals between the start of one sound element and the next. We calculate exact beats of a sequence using Fourier analysis and IOI analysis. Furthermore, we report on important parameters describing the variability in timing within a given sound sequence. Datasets were chosen to depict different possible rhythmic properties: Sciaena umbra sounds have a simple isochronous—metronome-like—rhythm. The /Kwa/ sound type emitted by Scorpaena spp. has a more complex rhythm, still presenting an underlying isochronous pattern. Calls of Ophidion rochei males present no rhythm, but a random temporal succession of sounds. This approach holds great potential for shedding light on important aspects of fish bioacoustics. Applications span from the characterization of specific behaviours to the potential discrimination of yet not distinguishable species.